Weak bonds, strong effects: enhancing the separation performance of UiO-66 toward chlorobenzenes via halogen bonding - Gulyaev, Roman; Semyonov, Oleg; Mamontov, Grigory V.; Ivanov, Alexey A.; Ivanov, Daniil M.; Kim, Minjun; Švorčík, Václav; Resnati, Giuseppe; Liao, Ting; Sun, Ziqi; Yamauchi, Yusuke; Postnikov, Pavel S.; et al. (ACS materials letters)
Halogen bonding (HaB) is a weak interaction that assists in the recognition of nucleophilic molecules. However, HaB elements are currently under-investigated as a part of functional materials in separation science. Herein, we develop a novel approach for introducing HaB elements into UiO-66 to fine-tune the adsorption properties toward chlorobenzenes (CBs). A series of UiO-66 containing various contents of 2-iodoterephtalic acid (I-TA) (0%, 33%, 50%, 67%, and 100%) was prepared, characterized, and applied for the selective removal of CB contaminants from nonchlorinated aromatic analogues that cannot be separated by common distillation. Investigation of the structure–property relationship revealed that the highest adsorption capacity was achieved in the case of UiO-66 loaded with 50% I-TA (UiO-66-Iopt), and this was attributed to the balance between the number of HaB elements and the surface area of the UiO-66 structure. According to density functional theory calculations, the formation of a conjugate between dichlorobenzene and UiO-66-Iopt was more energetically favorable (up to 1.7 kcal/mol) than that of the corresponding conjugate with UiO-66. The formation of HaBs was experimentally verified by UV–vis, Raman, and X-ray photoelectron spectroscopies. To obtain functional materials for separation applications, waste polyethylene terephthalate (PET) was used as a support and feedstock for the surface-assisted growth of UiO-66-Iopt. The as-prepared PET@UiO-66-Iopt exhibited a close-to-perfect selectivity and reusability for the separation of a wide range of CBs from nonchlorinated aromatic analogues.